Dynamics of a network mediated by IL-36 and involved in the pathogenesis of psoriasis - Pandey, Sneha; Tiwari, Syona; Basu, Sulagna; Mishra, Rajiv Kumar; Pandey, Rakesh (Frontiers in Network Physiology, 2024)
Pathogenesis of inflammatory, chronic, and common skin disease psoriasis involves immune cells, skin cells (keratinocytes), and cytokines secreted by them. Hyperproliferation and abnormal differentiation of keratinocytes are considered as one of the hallmarks of the disease. Roles of several cytokines such as TNFα, IL-15, IL-17, and IL-23 in psoriasis have been studied through mathematical/computational models as well as experiments. However, the role of pro-inflammatory cytokine IL-36 in the onset and progression of psoriasis is still elusive. To explore the role of IL-36, we construct a network embodying indirect cell-cell interactions of a few immune and skin cells mediated by IL-36 based on existing knowledge. Further, we develop a mathematical model for the network and perform a global sensitivity analysis. Our results suggest that the model is most sensitive to a model parameter that represents the level of the cytokine IL-36. In addition, a steady-state analysis of the model suggests that an increase in the level of IL-36 could lead to the hyper-proliferation of keratinocytes and, thus, psoriasis. Our analysis also highlights that the plaque formation and progression of psoriasis could occur through either a gradual or a switch-like increase in the population of keratinocytes. We propose that the switch-like increase would be due to a bistable behavior of the network towards either a psoriatic or healthy state, and could be used as a novel treatment strategy.